Decision Support Systems V - Big Data Analytics for Decision Making First International Conference, ICDSST 2015, Belgrade, Serbia, May 27-29, 2015, Proceedings - Delibašić, Boris; Hernández, Jorge E.; Papathanasiou, Jason; Dargam, Fátima; Zaraté, Pascale; Ribeiro, Rita; Liu, Shaofeng; Linden, Isabelle (Lecture Notes in Business Information Processing,, 2015)
This book constitutes the refereed proceedings of the First International Conference on Decision Support Systems Technology, ICDSST 2015, held in Belgrade, Serbia, in May 2015. The theme of the event was "Big Data Analytics for Decision-Making" and it was organized by the EURO (Association of European Operational Research Societies) working group of Decision Support Systems (EWG-DSS). The eight papers presented in this book were selected out of 26 submissions after being carefully reviewed by at least three internationally known experts from the ICDSST 2015 Program Committee and external invited reviewers. The selected papers are representative of current and relevant research activities in the area of decision support systems, such as decision analysis for enterprise systems and non-hierarchical networks, integrated solutions for decision support and knowledge management in distributed environments, decision support system evaluations and analysis through social networks, and decision support system applications in real-world environments. The volume is completed by an additional invited paper on big data decision-making use cases.